2011
DOI: 10.1111/j.1365-3148.2010.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a cell line panel as an alternative source of platelet antigens for a screening assay of anti‐human platelet antibodies

Abstract: Of the 12 sera containing HPA-1a (n = 2), HPA-3a (n = 6), HPA-6b (n = 3) or HPA-7 variant (n = 1) antibodies, all antibodies were detected and determined by our new method, except for two HPA-3a antibodies. One of the two antibodies was also negative for conventional platelet MAIPA, suggesting that the cell line panel might be used as an alternative source of platelet antigens in the MAIPA assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The MAIPA system, similar to MAIGA, is the gold standard for detecting HPA Abs [22], and we have shown that the cell line-based MAIPA (HP-MAIPA) system is also useful, because the preparation of a typed panel of platelets can be avoided [23]. In a previous study, the use of cell lines instead of panel platelets meant that MoAbs was not required, avoiding the risk of epitope competition between the MoAbs and human Abs for detection [24].…”
Section: Discussionmentioning
confidence: 97%
“…The MAIPA system, similar to MAIGA, is the gold standard for detecting HPA Abs [22], and we have shown that the cell line-based MAIPA (HP-MAIPA) system is also useful, because the preparation of a typed panel of platelets can be avoided [23]. In a previous study, the use of cell lines instead of panel platelets meant that MoAbs was not required, avoiding the risk of epitope competition between the MoAbs and human Abs for detection [24].…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the cell stabilization methods optimized and evaluated in this study may facilitate the distribution and use of transfected cells expressing low-incidence antigens, which could supplement and improve RBC-based antibody identification assays. Likewise, these methods may potentially simplify the detection of alloantibodies against human neutrophil antigens (HNA) [42, 43] or human platelet antigens (HPA) [44, 45] by means of HNA and HPA transfected cells, also available.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation and Western blot analysis was carried out according to a previously described method [31,33] using M280 magnetic beads (Invitrogen).…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…Transfections to produce K562 cells expressing HPA-4b were performed according to a previously described method [31,33] using retroviral particle carrying both GPIIb and GPIIIa containing HPA-4b genes. The cells were cloned by a limiting dilution method in the presence of 1.0 mg/mL puromycin and 0.8 mg/mL G418.…”
Section: Gene Transductionmentioning
confidence: 99%